Reduction and sterilization of eggs of gastrointestinal nematodes in goats dewormed with benzimidazoles anthelmintics - Vieira, Luiz da Silva; Gonçalves, Pedro Cabral; Costa, Carlos Alberto Fagonde; Berne, Maria Elisabeth Aires (Pesquisa Agropecuaria Brasileira, 2014)
The ovicide activity, “in vivo”, of the benzimidazoles: oxfendazole, fenbendazole, albendazole and thiabendazole on caprine gastrointestinal nematodes was determined and compared. Female goats naturally infected with gastrintestinal nematodes were medicated with oxfendazole (435 mg/kg), fenbendazole (5.0 mg/kg), albendazole (3.8 mg/kg) and thiabendazole (44.0 mg/kg). Feces were collected from the rectum to determine the number of eggs per gram (EPG) and to make fecal cultures, before medication and at subsequent periods from three to twelve hours after medication. Afterwards, collections were performed at intervals of 12 to 168 hours. Thiabendazole showed good activity on the reduction and sterilization of Strongyloides eggs but did not show the same activity against Haemonchus and Oesophagostomum. Oxfendazole, fenbendazole, and albendazole had good activity on the reduction and sterilization of the eggs of Trichostrongylus and Oesophagostomum, but did not have the same activity on Haemonchus and Strongyloides. Oxfendazole and thiabendazole were the only benzimidazoles that curbed the development and multiplication of the free living female Strongyloides in fecal cultures of dewormed animals.